BRAF inhibition with concomitant tumor treating fields for a multiply progressive pleomorphic xanthoastrocytoma. (30th April 2018) - Lukas, Rimas V; Merrell, Ryan T
Pleomorphic xanthoastrocytomas can be very resistant to treatment if they progress after standard therapy with surgery and radiation. We present the case of a patient with a multiply recurrent pleomorphic xanthoastrocytoma which demonstrated a sustained partial response to a combination regimen of the BRAF inhibitor vemurafenib and tumor treating fields. The regimen proved tolerable and efficacious in this case.